Aplikasi kaedah unsur terhingga secara dua dimensi dalam kejuruteraan angin - Siti Aminah Osman,; Abdul Khalim Abdul Rashid,; Taksiah Majid,; Khor, Eng Choon (2006)
The use of numerical prediction of wind loads onto the structural model by computer simulation offers certain advantages compared to the model tested in the wind tunnel. This study will look into the effectiveness and the suitability of Finite Element Method (FEM) through numerical simulation using FEMLAB software in the prediction of wind load effects to the structure. The wind flow and pressure distribution around the model are obtained from two-dimensional simulation of turbulence flow k-e. Two models of low rise buildings are chosen in order to compare the simulation results of the full scale and of the wind tunnel measurements. The predicted pressure coefficients Cp obtained from the simulation are then compared to previous studies using other methods such as Finite Difference Method (FDM) and Finite Volume Method (FVM). Overall results of these two models show that the application of Finite Element Method (FEM) in two dimensional simulation are acceptable and comparable to the other methods for the windward face. Whilst, for leeward face the predicted pressure coefficient (Cp) obtained are much larger compared to the real measurement